Why you don't get published: An editor's view - Bradbury ME (WILEY-BLACKWELL, 2012)
This paper uses content analysis to examine 66 reviews on 33 manuscripts submitted to Accounting and Finance. Selected extracts from reviews are provided to illustrate the issues considered important to reviewers. The main message is that papers need to be work-shopped and more care taken over editorial matters. A checklist for prospective authors is provided.
The definitive version is available at http://www.wileyonlinelibrary.com
Keywords: Publishing; Reviewing; Financial Accounting; Research Methodology; Editing